Urban Transformations in the U.S.A. and Transformations in Urban Cultural Studies (KULT_online, 2016)
The essay collection Urban Transformations in the U.S.A.: Spaces, Communities, Representations comprises contributions studying transformations in various urban settings and their cultural representations in the US from diverse transnational and interdisciplinary perspectives. The volume features different case studies and combines essays that both thematically and methodologically make for a very valuable and readable contribution to the field of urban studies.